DCD USANS and SESANS: a comparison of two neutron scattering techniques applicable for the study of large‐scale structures. (18th March 2013) - Rehm, Christine; Barker, John; Bouwman, Wim G.; Pynn, Roger
Abstract : This paper provides a comparison of the capabilities of two techniques for extending the range of conventional small‐angle neutron scattering (SANS) towards the micrometre length scale, namely the double‐crystal diffraction ultra‐small‐angle neutron scattering (DCD USANS) technique, which uses perfect silicon crystals in Bragg reflection, and spin‐echo SANS (SESANS), a method that uses the spin precessions of a polarized neutron beam. Both methods encode the scattering angle to very high precision. Based on round‐robin test measurements, the strengths and weaknesses of the two techniques are discussed with respect to the measurement of the particle size of monodisperse scatterers, and potential performance gains for state‐of‐the‐art DCD USANS and SESANS instruments are investigated.